Pemodelan Arsitektur Data pada Perguruan Tinggi (Studi Kasus : UMMagelang) - Mukhtar Hanafi; Ardhin Primadewi; Sunarni Sunarni (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Public services issue becomes major issue in the provision of public services, especially at higher education as one of the public sector in the field of education. Innovation is needed sistematically in developing service system especially on employee of higher education with good governance principle. This development is depend on Pusat Data dan Sistem Informasi UMMagelang. However, the control and development control of the system is autonomously assigned to each institutional. So the system is not developed based on the business function that is executed or the required data entity, but limited to the spontaneity of short-term needs. it needs an in-depth relationship analysis between the development of information systems with business functions running as well as data entities required. This research using Zachman Framework which has advantages in the depth of analysis on the data architecture as modelling method. This research relate 3 variables such as business functions, data entities and applications that facilitate the identification of positions that need to be addressed immediately.